READINESS OF UMKM TO PARTNER WITH LARGE BUSINESSES THROUGH FULFILLMENT OF PARTNERING REQUIREMENTS AND WORKSHOP SHARING SUCCESS STORY SME SUCCESS IN 2023 - Susanti; Kasmaniar; Ulfia; Radhiana; Asnariza (JURNAL KREASI RAKYAT, 2024)
Micro, Small and Medium Enterprises (MSMEs) have so far had a slight inability to access large business partners, due to limited information and access to large businesses. Apart from that, SMEs also do not have the documents needed to be submitted as a condition for making it easy to get business partners. medium and large businesses, the reason is that SMEs still have limited human resources, so their activities are more focused on production and marketing activities, and very limited human resources, information, and business networks. So assistants are needed to prepare the documents these micro and small businesses need, which will later be presented at workshops with potential partners, namely large businesses. Realizing the objectives of this mentoring activity, starts with identifying the MSME businesses that will be accompanied from the institutional aspect, including Legality, Business Institutional, Production Management, Marketing Management, Human Resources, and Business Capital aspects. The Micro Businesses assisted are; Sere Wangi Oil Business, King Soka Business, and Evy Handicraft Business. From the results of this month's mentoring, the three UKMs already have business documents for partnership, have met in workshops, and have collaborated with large businesses such as grocery supermarkets, Suzuya, and Kryad Hotels